Implementation of Entrepreneurship Education for Students at SMK Negeri 1 Sampit for the 2022/2023 Academic Year - Supian, Muhamad; Rahmawati, Novianti; Tartila, Yulita Ulfa (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research contains about how entrepreneurship education is implemented in class XI students at SMK Negeri 1 Sampit. Entrepreneurship education plays an important role in creating the next generation to be ready for future economic challenges. This study aims to determine implementation in class XI students of SMK Negeri 1 Sampit. This research is qualitative research. The subject of this research is a class XI subject teacher at SMK Negeri 1 Sampit. Meanwhile, the informants in this research were three class XI students. Data collection techniques in this research are interviews and documentation. Data analysis techniques through data reduction processes, data presentation, and data verification. To test the validity of the data using triangulation of sources and methods. The results of this research are (1) There are 6 aspects out of 7 aspects of implementing entrepreneurship education which are implemented in class XI students at SMK Negeri 1 Sampit. Of these 6 aspects, 5 aspects can be implemented effectively. The entrepreneurship education that has been implemented is: a). integrated entrepreneurship education in extracurricular activities, b), entrepreneurship education through self-development, c). changes in the implementation of entrepreneurship learning from theory to practice, d). integrating entrepreneurship education into materials or textbooks, e). integrating entrepreneurship education through school culture. The implementation of entrepreneurship education for class (2) entrepreneurship education is not implemented in the integration of entrepreneurship education through local content because local content subjects are not available in the 2013 curriculum.